Assessment of Genetic Variation within Commercial Iranian Pomegranate (Punica granatum L.) Cultivars, Using ISSR and SSR Markers - Meysam Madadi; Zabihollah Zamani; Reza Fatahi (Turkish Journal of Agriculture: Food Science and Technology)
Pomegranate is one of the most important horticultural crops in Iran, and has been cultivated for thousands of years in this country. At this period due to selection of superior cultivars from nature or mutation emerged in these cultivars, and their vegetative propagation, substantial genetic variation has occurred within and among the cultivars. Thus, each cultivar may consist of different clones. According to this issue, diversity within four commercial cultivars of pomegranate was analyzed. Two molecular marker systems including ISSR and SSR were used to evaluate variability between 36 samples of four commercial cultivars. ISSR markers produced 114 amplification products, out of which 97 were polymorphic (83.23%). Mean resolving power was 2.96 for ISSR markers. 19 SSR molecular markers were used, 15 of which amplified polymorphic products, while the remaining ones monomorphic., The number of polymorphic alleles per locus ranged from two to four (average 3.6). The observed and expected heterozygosities ranged from 0.04 to 0.92 and 0.14 to 0.62, respectively. In addition, mean polymorphic information content was 0.45 for SSR loci. Our results showed that commercial Iranian pomegranate have different clones. Therefore, ISSR and SSR markers can be a useful tools for detecting clones of each cultivar.